The Hidden Curriculum: Gender Roles in Textbooks : A Literature review - Kovalainen, Aino (My University, 2025)
This literature review aims to explore the portrayal of gender roles within educational textbooks, focusing on how gender identities and behaviors are depicted. The study will analyze textbooks to identify repeated patterns and representations of gender, assessing whether these depictions reinforce traditional gender norms or promote a more inclusive understanding of gender diversity. By examining how genders are represented, this study seeks to discover the hidden messages about gender that textbooks convey to students and educators.
Keywords: gender roles, textbooks, stereotypes, primary education